Pengaruh Investor Sentiment, Relative Strength Index, Analyst Recommendation, dan Net Foreign Flow terhadap Return Saham: Studi Pada Perusahaan Yang Masuk Dalam Indeks LQ45 Periode 2020-2024 - Haliza Yolanda Yustanti; Erman Denny Arfinto (Diponegoro Journal of Management, 2026)
The Indonesian capital market is increasingly characterized by the dominance of retail investors and the growing influence of investor behavior in stock price formation. However, prior studies have largely emphasized fundamental factors, while behavioral and market-dynamic factors remain less comprehensively examined. This study analyzes stock return formation of companies included in the Indeks LQ45 during 2020–2024 from a behavioral finance perspective.This study employs a quantitative approach using secondary panel data of companies listed in the LQ45 Index with quarterly observations from 2020 to 2024. The research sample consists of 37 companies that meet the data completeness criteria. Panel data regression with a fixed effect model is applied as the main analytical method using STATA software to obtain statistically consistent and robust estimation results.The results indicate that investor sentiment, the Relative Strength Index, and analyst recommendations have a positive and significant effect on stock returns. In contrast, Net Foreign Flow does not have a significant effect on stock returns, suggesting that foreign investor capital flows tend to be passive and do not play a major role in driving stock price movements. Overall, the findings confirm that stock return formation in the Indonesian capital market is more strongly influenced by internal market factors and investor behavior than by foreign capital flows.